Targeting cattle-borne zoonoses and cattle pathogens using a novel trypanosomatid-based delivery system. - G Adam Mott; Raymond Wilson; Anuruddika Fernando; Ailie Robinson; Paula MacGregor; David Kennedy; Dick Schaap; Jacqueline B Matthews; Keith R Matthews (PLoS Pathogens)
Trypanosomatid parasites are notorious for the human diseases they cause throughout Africa and South America. However, non-pathogenic trypanosomatids are also found worldwide, infecting a wide range of hosts. One example is Trypanosoma (Megatrypanum) theileri, a ubiquitous protozoan commensal of bovids, which is distributed globally. Exploiting knowledge of pathogenic trypanosomatids, we have developed Trypanosoma theileri as a novel vehicle to deliver vaccine antigens and other proteins to cattle. Conditions for the growth and transfection of T. theileri have been optimised and expressed heterologous proteins targeted for secretion or specific localisation at the cell interior or surface using trafficking signals from Trypanosoma brucei. In cattle, the engineered vehicle could establish in the context of a pre-existing natural T. theileri population, was maintained long-term and generated specific immune responses to an expressed Babesia antigen at protective levels. Building on several decades of basic research into trypanosomatid pathogens, Trypanosoma theileri offers significant potential to target multiple infections, including major cattle-borne zoonoses such as Escherichia coli, Salmonella spp., Brucella abortus and Mycobacterium spp. It also has the potential to deliver therapeutics to cattle, including the lytic factor that protects humans from cattle trypanosomiasis. This could alleviate poverty by protecting indigenous African cattle from African trypanosomiasis.